Alkaline earth metal compounds of methylpyridinato beta-diketiminate ligands and their catalytic application in hydroboration of aldehydes and ketones - Yadav, Sandeep; Dixit, Ruchi; Bisai, Milan Kumar; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2018)
Ever increasing demand for green and sustainable chemical processes has set up a drive to replace transition metals with earth-abundant, nontoxic, and environmentally benign alternatives. In this regard, the alkaline earth metal complexes have attracted significant attention. Herein, we have used a beta-diketiminato ligand with methyl-pyridine side arm to synthesize magnesium (1) and calcium (2) compounds. The constitutions of 1 and 2 have been confirmed by single crystal X-ray studies, which show that the magnesium and calcium atom in 1 and 2 possesses octahedral geometry. Subsequently, we have used them as catalysts (1 mol %) for hydroboration of a wide range of aldehydes using pinacolborane (HBpin) at room temperature. The strategy has further been extended to ketones with 2 mol % catalyst loading. DFT calculations have been performed to understand the mechanism.